PREDIKSI PUNCAK KEMATANGAN BUAH NAGA MELALUI PENGUKURAN GULA REDUKSI DENGAN METODE NELSON-SOMOGYI - Alimuddin - (JURNAL KIMIA MULAWARMAN, 2012)
Prediction of dragon fruit maturation peak by measuring reductor sugar with nelson-somogyi method have been done. Prediction was done by using three modes which are experimental result, regression model and first derivation. Age of the fruit which used in this research were 1, 3, 5 and 7 weeks old. Based on the result of this research can be concluded that maturation peak of dragon fruit happens at between 5 until 6 weeks old.Keywords: Dragon Fruit, Reductor Sugar and Nelson-Somogyi Method.